IMF essays from a time of crisis : the international financial system, stabilization, and development - Fischer, Stanley (MIT Press, 2004)
Stanley Fischer served as First Deputy Managing Director of the International Monetary Fund from 1994 to 2001. IMF Essays from a Time of Crisis collects sixteen essays written for the most part during his time at the IMF, each updated with Fischer's later reflections on the issues raised. The IMF drew much criticism for some of its actions during Fischer's tenure, and he vigorously defends the "battlefield medicine" practiced by the IMF during a series of economic crises, which included the problems of economic transition in the former Soviet bloc and the Asian financial crisis. Fischer addresses the subsequent calls for reform of the international financial system and makes the case for the IMF as an international lender of last resort. The first section of essays, "The Role of the IMF and the Reform of the International Financial System," considers the IMF's role in the international financial system in light of the crises of the 1990s. The second section, "Macroeconomic Policy, Stabilization, and Transition," examines such topics as exchange rate regimes, inflation, and Eastern Europe's relation to the European Union. The final section, "Poverty and Development," reflects Fischer's basic belief that economic policies should explicitly target poverty reduction. These engaging and accessible essays will appeal not only to economics students, economists, and policymakers but also to the general reader interested in the international monetary system.